2021
DOI: 10.5530/pj.2021.13.124
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Antioxidant Activities Evaluation of Origanum vulgare (L.) Stem Bark Extracts

Abstract: The present study aimed to evaluate phytochemical and antioxidant activity (in vitro and in vivo) of Origanum vulgare (L.) ethanolic extract. The phytochemical test was assessed using the Clule method in ethanol, ethyl acetate, and hexane. In vitro evaluation of antioxidant activity was determined by radical scavenging assay using DPPH (2,2-diphenyl-1-picrylhydrazyl) as an artificial free radical activity. In vivo test was conducted to evaluate the effect of malondialdehyde (MDA) level in blood plasma during m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[ 14 15 16 ] Based on the comparison of antioxidant activity, antioxidant intensity was categorised such as strong (IC 50 <50 µg/mL), active (IC 50 50–100 µg/mL), moderate (IC 50 101–250 µg/mL), weak (IC 50 251–500 µg/mL), and inactive (IC 50 >500 µg/mL). [ 17 18 ] From the result mentioned above, the IC 50 value of PEE is categorized as moderate antioxidant intensity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 15 16 ] Based on the comparison of antioxidant activity, antioxidant intensity was categorised such as strong (IC 50 <50 µg/mL), active (IC 50 50–100 µg/mL), moderate (IC 50 101–250 µg/mL), weak (IC 50 251–500 µg/mL), and inactive (IC 50 >500 µg/mL). [ 17 18 ] From the result mentioned above, the IC 50 value of PEE is categorized as moderate antioxidant intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, plants and natural products continue to be important sources of novel bioactive compounds [7][8][9][10]. Several studies have identified, quantified, and classified bioactive compounds, such as flavonoids, saponins, terpenes, and steroids, with potential uses as antioxidant, anti-inflammatory, and antimicrobial compounds [11][12][13][14][15][16]. The genus Agave consists of approximately 200 species; 150 are in Mexico, with 119 endemics [17][18][19].…”
Section: Introductionmentioning
confidence: 99%